Evaluation of the toxicity of glucocorticoids in patients with autoimmune blistering disease using the Glucocorticoid Toxicity Index: A cohort study - Liang, Yicong; Zeng, Faith A.P.; Sheriff, Tabrez; Wilson, Anna; Bilgic, Asli; Feng, Grant; Stone, John H.; Murrell, Dedee F. (JAAD international, 2022)
Glucocorticoids are the mainstay of treatment for autoimmune blistering diseases (AIBDs). The Glucocorticoid Toxicity Index (GTI) is a novel, outcome-based glucocorticoid-induced adverse effects monitoring instrument. To investigate whether the GTI score was able to accurately quantify the glucocorticoid-induced toxicity in patients with AIBDs. The prospective cohort study included patients with confirmed diagnoses of AIBDs (group1, currently receiving glucocorticoids; and group 2, had glucocorticoids ceased earlier). Data were collected minimally at baseline (V1) and 3 months (V2). Further data from patients who were able to complete the follow-up visits at 6 months (V3) and 12 months (V4) amid the COVID-19 pandemic were also included. GTI scores were calculated after data collection. Analysis of data from V1 and V2 found a linear correlation between GTI score and prednisone doses (P < .05) and a significant difference in GTI scores between group1 and group 2 (P < .05). Data from V3 and V4 suggested that GTI scores continued to rise progressively alongside increasing cumulative prednisone dose. Small sample size, further exacerbated by the COVID-19 pandemic. Single-center study. The GTI sensitively and specifically captured the changes in glucocorticoids toxicity over time among patients with AIBDs. The GTI could be a feasible tool that can be used in future clinical trials as a glucocorticoid-induced toxicity outcome measure.